2020
DOI: 10.1182/bloodadvances.2019001053
|View full text |Cite|
|
Sign up to set email alerts
|

KIR B donors improve the outcome for AML patients given reduced intensity conditioning and unrelated donor transplantation

Abstract: Natural killer (NK) cell recognition and killing of target cells are enhanced when inhibitory killer immunoglobulin-like receptors (KIR) are unable to engage their cognate HLA class I ligands. The genes of the KIR locus are organized into either KIR B haplotypes, containing 1 or more activating KIR genes or KIR A haplotypes, which lack those genes. Analysis of unrelated donor (URD) hematopoietic cell transplants (HCT), given to acute myeloid leukemia (AML) patients between 1988 and 2009, showed that KIR B hapl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 27 publications
1
38
2
1
Order By: Relevance
“…KIRs have been shown to be clinically significant in allogeneic hemopoietic stem cell transplant (HSCT) treatments for acute myeloid leukemia (AML) in cases of KIR profile mismatches where the inhibitory KIRs on the NK cells derived from the stem cell donor do not encounter their cognate ligands on the transplant recipient's AML blasts. In these cases, NK cells become activated and kill their targets more effectively leading to a survival benefit to AML patients ( 35 , 36 ). These findings have been adopted in practice, as when otherwise similarly HLA-matched allogeneic or haploidentical HSCT donors are available, HSCT donor selection algorithms consider KIR profiles as a donor selection criteria ( 35 , 37 39 ).…”
Section: Introductionmentioning
confidence: 99%
“…KIRs have been shown to be clinically significant in allogeneic hemopoietic stem cell transplant (HSCT) treatments for acute myeloid leukemia (AML) in cases of KIR profile mismatches where the inhibitory KIRs on the NK cells derived from the stem cell donor do not encounter their cognate ligands on the transplant recipient's AML blasts. In these cases, NK cells become activated and kill their targets more effectively leading to a survival benefit to AML patients ( 35 , 36 ). These findings have been adopted in practice, as when otherwise similarly HLA-matched allogeneic or haploidentical HSCT donors are available, HSCT donor selection algorithms consider KIR profiles as a donor selection criteria ( 35 , 37 39 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of these in vitro data, NK cell populations characterized by a large size of the alloreactive subset and by a NCR bright phenotype are likely to exert an optimal anti-leukemia activity. In addition, B/x KIR genotype and high B content value, the presence of KIR2DS1 E/U, and the presence of NKG2C, indicating a receptor repertoire well equipped with activating receptors, were positively considered in our donor selection criteria [4,12,35,37,39,51,52]. Unexpectedly, no significant correlation with LFS was observed considering donor NK alloreactivity, KIR genotype, B-content score and KIR2DS1 E/U [34].…”
Section: Discussionmentioning
confidence: 88%
“…Cooley et al observed that patients with AML with KIR-B/x donors experienced a 30% improvement in RFS compared with those with A/A donors ( 40 ). Subsequently, many further investigations confirmed this beneficial effect of the KIR-B haplotype on relapse and survival in patients with hematological malignancies ( 50 , 51 , 57 , 67 , 72 , 76 , 79 , 81 , 85 , 88 92 , 96 , 98 , 101 104 ). Five of these studies reported that the protection effects mainly existed in the KIR Cen-B locus ( 67 , 88 , 91 , 92 , 96 ).…”
Section: Kir and Transplant Outcomesmentioning
confidence: 85%